2020
DOI: 10.26434/chemrxiv.12480974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ORR in Ca2+ Containing DMSO: Reaction Mechanism, Electrode Surface Characterization and Redox Mediation

Abstract: In this study we strengthen our fundamental understanding of the underlying reactions of a possible Ca-O<sub>2</sub> battery using a DMSO based electrolyte. Employing the rotating ring disc electrode, we find a transition from a mixed process of O<sub>2</sub><sup>-</sup> and O<sub>2</sub><sup>2-</sup> formation to an exclusive O<sub>2</sub><sup>-</sup> formation at gold electrodes. We will show that in this system Ca-superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…This work strongly focuses on the ORR/OER mechanism in Ca 2+ ‐containing DMSO and the influence of the surface structure (single crystal orientation on the one hand and high roughness factors on the other). It supplements a previous study in which already a transition from mixed O2- and O22- formation to exclusively O2- formation was observed on smooth electrodes [29] . The study further showed that the blocking thin film mainly consist of Ca(O 2 ) 2 , CaO 2 and CaO (identified by XPS) and is formed on Au and Pt electrodes.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…This work strongly focuses on the ORR/OER mechanism in Ca 2+ ‐containing DMSO and the influence of the surface structure (single crystal orientation on the one hand and high roughness factors on the other). It supplements a previous study in which already a transition from mixed O2- and O22- formation to exclusively O2- formation was observed on smooth electrodes [29] . The study further showed that the blocking thin film mainly consist of Ca(O 2 ) 2 , CaO 2 and CaO (identified by XPS) and is formed on Au and Pt electrodes.…”
Section: Introductionsupporting
confidence: 88%
“…Note that in the first sweeps up to 0.4 V oxidation of this adsorbate is slow and remains incomplete, whereas in subsequent sweeps the maximum current is at 0.25 V (peak potential). This indicates a nucleation and growth behavior for the free sites, as observed earlier for Ca 2+ electrolytes on smooth Au electrodes [29] and for Na + electrolytes on smooth Pt (but not on Au) [40]…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations